Can the Early Osteoarthritis Questionnaire (EOAQ) Reflect the Biomechanical Characteristics of Knee Osteoarthritis? - Weon, Young-soo; Ha, Sung-min (Journal of Musculoskeletal Science and Technology, 2024)
Background The Early Osteoarthritis Questionnaire (EOAQ) emerges as a tool for assessing knee osteoarthritis (OA) at its initial stages, offering a potential avenue for early detection and intervention. However, it remains unclear whether the EOAQ accurately reflects biomechanical changes in individuals at risk for knee OA. Purpose To determine whether EOAQ can reflect the biomechanical characteristics that appear during functional movements in individuals at risk for early knee OA. Study design Cross-sectional study Methods Forty-three manufacturing workers aged 40 to 70 years participated in this study and a total 86 legs were recruited. Through the EOAQ, the subjects were divided into an experimental group with a risk of early OA and a control group. There were 42 legs in the experimental group and 44 legs in the control group. Subjects performed the 4 functional movements: one leg standing (OLS), sit to stand (STS), stair up (SU) and down (SD). During functional movements, horizontal displacement of pelvis (PHD), knee (KHD), and ankle (AHD) were video-recorded and analyzed using Kinovea software. Independent t-test was used to compare the characteristics between groups. Results The experimental group showed greater PHD, KHD, and AHD during 4 functional movements (OLS, STS, SU, and SD) than the control group (p<0.05), except for AHD during STS. Conclusions The results of this study suggest that EOAQ effectively reflects lateral horizontal displacement, a biomechanical characteristic of knee OA. The use of the EOAQ to diagnose and prevent early knee OA is recommended. Background The Early Osteoarthritis Questionnaire (EOAQ) emerges as a tool for assessing knee osteoarthritis (OA) at its initial stages, offering a potential avenue for early detection and intervention. However, it remains unclear whether the EOAQ accurately reflects biomechanical changes in individuals at risk for knee OA. Purpose To determine whether EOAQ can reflect the biomechanical characteristics that appear during functional movements in individuals at risk for early knee OA. Study design Cross-sectional study Methods Forty-three manufacturing workers aged 40 to 70 years participated in this study and a total 86 legs were recruited. Through the EOAQ, the subjects were divided into an experimental group with a risk of early OA and a control group. There were 42 legs in the experimental group and 44 legs in the control group. Subjects performed the 4 functional movements: one leg standing (OLS), sit to stand (STS), stair up (SU) and down (SD). During functional movements, horizontal displacement of pelvis (PHD), knee (KHD), and ankle (AHD) were video-recorded and analyzed using Kinovea software. Independent t-test was used to compare the characteristics between groups. Results The experimental group showed greater PHD, KHD, and AHD during 4 functional movements (OLS, STS, SU, and SD) than the control group (p<0.05), except for AHD during STS. Conclusions The results of this study suggest that EOAQ effectively reflects lateral horizontal displacement, a biomechanical characteristic of knee OA. The use of the EOAQ to diagnose and prevent early knee OA is recommended. KCI Citation Count: 0